Domination and Global Domination Of Some Operations On Product Fuzzy Graphs - Haifa A. A.; M.Q Shubatah (IJRDO -JOURNAL OF MATHEMATICS, 2020)
In this paper, Some operation in product fuzzy graphs are introduced and investigated. The domination γ(G) and global domination γg(G) number of such operations are introduced and some bounds of γ(G) and γg(G) were given with some suitable examples.